Single-Shot Imaging Without Reference Wave Using Binary Intensity Pattern for Optically-Secured-Based Correlation - Chen, Wen (IEEE photonics journal, 2016)
In this paper, a novel method is proposed to optically verify the decoded images via single-shot imaging without reference wave using a binary intensity pattern. Optical imaging without reference wave is applied based on double random phase encoding (DRPE), and the recorded intensity pattern is further compressed, which contains only two quantization levels (i.e., 0 and 1). During the decoding, an iterative phase retrieval algorithm is developed and applied. It is demonstrated that decoded images do not visually render the input information due to the designed optical encoding strategy using only one binary intensity pattern, and optical verification is further conducted to effectively verify the decoded images. An additional security layer is established for the developed optical system, since optical verification is conducted based on optical encoding systems without direct observation of input information from the decoded images. It is the first to report the use of only one 1-bit intensity pattern in the DRPE system based on single-shot imaging without reference wave for secured verification via optical correlation.